Use of natural antioxidants in dairy and meat products: a review of sensory and instrumental analyses - Cottone, Elyse (Kansas State University, 2009)
Oxidative deterioration is a significant contributing factor to the limited shelf life of foods containing lipids. The lipids in meats and dairy products make them susceptible to oxidation, limiting the amount of time that such products can be stored before a change in the sensory properties is evident. The use of rosemary oleoresin in meat products and fried foods has been extensively researched and used in commercialized foods. Since dry cheese and dairy products also contain lipids that are highly susceptible to oxidation, the use of a natural rosemary oleoresin may be beneficial in increasing the shelf life and sensory acceptability of these products as well. The overall objective of this report was to review the uses of a natural antioxidant, rosemary oleoresin, to inhibit oxidation and sensory changes in dairy and meat products and determine which areas need further study.
Keywords: oleoresin; dairy; natural antioxidants; meats; sensory quality; chemical quality; Agriculture, Food Science and Technology (0359)